IMPROVING THE QUALITY OF LIFE OF PATIENTS WITH CARDIOVASCULAR DISEASES - Durdona Akbaralievna Raimova; Mirzokhid Sabitzhanovich Musakov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Cardiovascular diseases are the most common cause of death in industrialized countries. These include coronary heart disease, cerebrovascular disease, and peripheral arterial disease. For many years, cardiovascular disease (CVD) has firmly held the leading position among all causes of death worldwide. Three risk factors for cardiovascular disease—hypertension, smoking, and dyslipidemia—are known to account for more than 75% of all cardiovascular mortality. The likelihood of developing coronary heart disease and other cardiovascular diseases increases with the number and severity of these risk factors [1]. The most significant forms of cardiovascular disease in terms of morbidity and mortality are coronary heart disease and stroke, as they account for more than 70% of all cardiovascular deaths. Therefore, the fight against cardiovascular diseases and their causes is a primary goal of cardiology [2]. Cardiovascular diseases affect a large number of the population. According to the WHO, the main risk factors for the development of heart disease and stroke are poor nutrition, physical inactivity, tobacco use, and harmful alcohol consumption. This pathology occurs at an earlier age than in previous years and is the leading cause of death worldwide. A third of all deaths are due to cardiovascular diseases. The most common cardiovascular diseases include coronary heart disease, hypertension, and cerebrovascular lesions. Men die significantly more often from myocardial infarction than women. One of the most dangerous diagnoses is acute coronary syndrome. In addition to damage to health and life, cardiovascular diseases cause significant annual economic losses to the state, amounting to 3.2%. [3]. Achieving this goal is possible with widespread citizen engagement in healthy lifestyle practices. This includes creating conditions for maintaining and promoting a healthy lifestyle, reducing the impact of the main risk factors (RF) for non-communicable diseases (NCDs), screening and early detection of diseases, and engaging workers in health promotion programs [4].